Initier au projet par le jeu. Evaluation d'une expérimentation en école d'ingénieurs - Caroline Verzat
This paper is based on an action-research, conducted with students in engineering at the Ecole Centrale de Lille in 2006. The aim of this paper is to evaluate the effects of a construction game using spaghettis on the students' capacity to suggest creative ideas, to build and manage their team work and to learn from experience. These effects are measured through the immediate feedbacks on the game and the management of real project teams after the game. Items such as the composition of the teams, the origins of their subject six weeks later and self-evaluations of team management after 3 month are examined.